Efficacy of Eculizumab in a patient with immunoadsorption-dependent catastrophic antiphospholipid syndrome: a case report - Kronbichler, Andreas; Kirschfink, Michael (Medicine, 2014)
Catastrophic antiphospholipid syndrome (CAPS) is a rare but devastating complication in patients with antiphospholipid syndrome (APS) with a high morbidity and mortality. - We describe a case of a 30-year old female patient with immunoglobulin A (IgA) deficiency who underwent splenectomy because of idiopathic thrombocytopenic thrombocytopenia. Subsequently, an APS and finally systemic lupus erythematosus was diagnosed. After an uncomplicated pregnancy that was terminated by cesarean section, the patient developed severe CAPS with cerebral, myocardial, renal, and pulmonary involvement. - Because of IgA deficiency, standard therapy consisting of plasmapheresis and intravenous immunoglobulins in addition to steroids was not tolerated. After 8 sessions of immunoadsorption (IAS), massive pulmonary hemorrhage was controlled but relapsed twice whenever IAS was terminated. As other immunosuppressive agents were considered dangerous because of the risk of infections in the face of severe hypogammaglobulinemia, we administered eculizumab, an inhibitor of the terminal complement pathway, which led to a persistent control of her disease. Interestingly, eculizumab therapy was associated with a further decline of complement C3 and C4 serum levels. The patient developed a subsequent flare of her systemic lupus erythematosus, potentially indicating that complement inhibition by eculizumab is not effective in preventing lupus flares. - Taken together, we describe a unique case of life-threatening and difficult-to-treat CAPS with a good clinical response after terminal complement complex inhibition with eculizumab. Further controlled trials are necessary to investigate the value of eculizumab in patients with CAPS.
Gesehen am 23.10.2020